Encouraging Sustainable MSME Performance in Bali Province Through Circular Economy and Innovation - Yuniarta, Gede Adi; Purnamawati, I Gusti Ayu (Jurnal Media Informatika, 2024)
This study aims to examine the relationship between the implementation of a circular economy and innovation in the sustainable performance of MSMEs in Bali Province. To that end, hypothesis testing was conducted using Structural Equation Modeling (SEM) analysis based on data obtained from a questionnaire with a Likert scale distributed to 300 respondents consisting of MSME owners or managers in Bali. This study tests four main hypotheses related to the implementation of circular economy principles, innovation, and sustainable MSME performance. This study shows that the implementation of a circular economy and innovation has great potential to improve the performance and sustainability of MSMEs in Bali Province. MSMEs that implement circular economy principles can not only reduce costs and optimize resources, but also contribute to environmental preservation and social welfare. Therefore, the implementation of a circular economy and innovation should be seen as an important strategy to encourage more sustainable MSMEs and increase their competitiveness in the global market